Evidence of the involvement of a cyclase gene in the biosynthesis of ochratoxin A in Aspergillus carbonarius - Ferrara, Massimo; Gallo, Antonia; Cervini, Carla; Gambacorta, Lucia; Solfrizzo, Michele; Baker, Scott E.; Perrone, Giancarlo (MDPI, 2021)
Ochratoxin A (OTA) is a well-known mycotoxin with wide distribution in food and feed. Fungal genome sequencing has great utility for identifying secondary metabolites gene clusters for known and novel compounds. A comparative analysis of the OTA-biosynthetic cluster in A. steynii, A. westerdijkiae, A. niger, A. carbonarius, and P. nordicum has revealed a high synteny in OTA cluster organization in five structural genes (otaA, otaB, ota, otaR1, and otaD). Moreover, a recent detailed comparative genome analysis of Aspergilli OTA producers led to the identification of a cyclase gene, otaY, located in the OTA cluster between the otaA and otaB genes, encoding for a predicted protein with high similarity to SnoaLs domain. These proteins have been shown to catalyze ring closure steps in the biosynthesis of polyketide antibiotics produced in Streptomyces. In the present study, we demonstrated an upregulation of the cyclase gene in A. carbonarius under OTA permissive conditions, consistent with the expression trends of the other OTA cluster genes and their role in OTA biosynthesis by complete gene deletion. Our results pointed out the involvement of a cyclase gene in OTA biosynthetic pathway for the first time. They represent a step forward in the understanding of the molecular basis of OTA biosynthesis in A. carbonarius.
Keywords: OTA; biosynthetic cluster; SnoaL domain; polyketide cyclases; CRISPR/Cas9